Caused accompanied motion bringing and taking events in a cross-linguistic perspective - Margetts, Anna; Hellwig, Birgit, 1970-; Riesberg, Sonja (Typological studies in language, 2022)
"This volume investigates the linguistic expression of directed caused accompanied motion events, including verbal concepts like BRING and TAKE. Contributions explore how speakers conceptualise and describe these events across areally, genetically, and typologically diverse languages of the Americas, Austronesia and Papua. The chapters investigate such events on the basis of spoken language corpora of endangered, underdescribed languages and in this way the volume showcases the importance of documentary linguistics for linguistic typology. The semantic domain of directed caused accompanied motion shows considerable crosslinguistic variation in how meaning components are conflated within single lexemes or distributed across morphemes or clauses. The volume presents a typology of common patterns and constraints in the linguistic expression of these events. The study of crosslinguistic event encoding provided in this volume contributes to our understanding of the nature, extent and limits of linguistic and cognitive diversity"--